2002
DOI: 10.1128/aem.68.2.738-744.2002
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Transfer of the Plant Virulence Gene, nec1 , and Flanking Sequences among Genetically Distinct Streptomyces Strains in the Diastatochromogenes Cluster

Abstract: Evidence for the horizontal transfer of a pathogenicity island (PAI) carrying the virulence gene nec1 and flanking sequences among Streptomyces strains in the Diastatochromogenes cluster is presented. Plant-pathogenic, thaxtomin-producing Streptomyces strains, previously classified as S. scabiei based on the conventionally used phenotypic characteristics, were found to be genetically distinct from the type strain of S. scabiei based on DNA relatedness and 16S rDNA sequence analysis. Pairwise DNA-DNA hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 31 publications
7
75
1
Order By: Relevance
“…4). This finding substantiates an earlier report that S. bottropensis may include pathogenic strains (Bukhalid et al 2002). The 16S rDNA gene from an isolate of a third ribotype was sequenced; it is most closely related to two nonpathogenic isolates also derived from potato CS lesions, ME02-6987.2a (GenBank accession EU080949.1) and AK03-4B (EU080939.1), and to S. achromogenes subspecies tomaymyceticus.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…4). This finding substantiates an earlier report that S. bottropensis may include pathogenic strains (Bukhalid et al 2002). The 16S rDNA gene from an isolate of a third ribotype was sequenced; it is most closely related to two nonpathogenic isolates also derived from potato CS lesions, ME02-6987.2a (GenBank accession EU080949.1) and AK03-4B (EU080939.1), and to S. achromogenes subspecies tomaymyceticus.…”
Section: Discussionsupporting
confidence: 72%
“…With the advent of molecular genetic characterization of CS-causing species, it became apparent that Streptomyces scabies was a complex of species (BouchekMechiche et al 2000;Bukhalid et al 2002;Doering-Saad et al 1992;Healy and Lambert 1991;Takeuchi et al 1996). Morphological, physiological and molecular evidence currently supports the designation of about ten CS-causing species known from one or more geographic locations around the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is sound evidence that the evolution of pathogenesis involves the acquisition of virulence-related genes (including entire PAIs) via HGT (Reid et al 2000;Bukhalid et al 2002), some studies reported that PAIs have been retained within pathogen species over evolutionary time (e.g., Escobar-Paramo et al 2003;Gressmann et al 2005;Rohmer et al 2004;Nallapareddy et al 2005). We do not know why some PAIs are evolutionary stable whereas others are not, but our results provide one possible explanation: Unlike a PAI acquired via recent HGT, an evolutionary stable PAI can work as a large reservoir of preexisting genetic variation in this highly polymorphic species.…”
Section: Discussionmentioning
confidence: 99%
“…Potato scab is a disease of major economic importance in most potato-producing areas of the world (Lambert and Loria, 1989). The genes that encode the thaxtomin biosynthetic pathway appear to lie on a pathogenicity island that was transmitted to Streptomyces species, resulting in the emergence of new pathogenic species in agricultural production systems (Healy et al, 1999(Healy et al, , 2000Bukhalid et al, 2002). The pathogenicity of various S. scabies isolates is correlated with their ability to produce thaxtomin A (King et al, 1991;Loria et al, 1995;Goyer et al, 1998;Kinkel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%